Prospects for the Efficiency of Financial Markets in the Era of Artificial Intelligence Technology 2018-2030 Opportunities and challenges - moussaoui, assia (Journal of Research in Finance and Accounting, 2025)
The study aims to present and analyze the relationship between Artificial intelligence and financial market efficiency By addressing the theoretical and historical framework of artificial intelligence in financial markets, and the financial markets efficiency theory as well as highlighting the importance of Artificial Intelligence in enhancing financial markets efficiency by utilizing the most recent AI technologies such as Natural language processing (NLP) programs, Sentiment analysis (SA), Explainable Artificial Intelligence (XAI), and the most important finding of the study is that artificial intelligence provides three essential elements for financial markets: information efficiency, reduction of trading costs, and mitigation of risks in financial markets, which are the basis of Fama’s financial markets efficiency theory. There are also multiple challenges that face these markets, most importantly the black box problem,...., wrong signals. The most significant aspect that will distinguish the future of these financial markets is the increasing reliance on AI-driven algorithmic trading. This trend may provide an alternative interpretation of market efficiency theory in the presence of artificial intelligence, at least until 2030.